ANALISIS RANTAI PASOK CRUDE PALM OIL (CPO) DI KABUPATEN PASAMAN BARAT - Lisa Nesti; Firwan Tan; Rika Ampuh Hadiguna (Agripita: Jurnal Agribisnis dan Pembangunan Pertanian, 2017)
which has a tendency to increase production from year to year. The purpose of this study is to get an overview of CPO supply chain in West Pasaman by reviewing all activities covering the flow of goods, information flow and cash flow that occurs in the supply chain. The results showed that in the flow of goods, there are three forms of the flow of supplies palm fruits to Agro Industries are distinguished by palm fruits of independent smallholders, farmers and palm fruits from the nucleus, while the flow of information includes feedback information received and given by each supply chain actors CPO include farmers, mill palm oil processing, expedition CPO, CPO mill and factory CPO refinery dan export while the cash flow coming from downstream (end consumer) to the upstream in the form of price realization of commodities purchase and sale agreement in the supply chain.